FUNGSI DEIKSIS PRONOMINA DEMONSTRATIF (ISIM ISYARAH) DALAM AL-QUR’AN (STUDI PRAGMATIK) - Muhammad Hanif Muzhaffar; Hajidah, Gina Najjah (Institut Kariman Wirayudha Sumenep, 2025)
This study aims to analyze the function of demonstrative pronouns and the deictic function of demonstrative pronouns found in the Qur'an. The method used in conducting this research is a qualitative-descriptive method with data collection techniques in the form of library studies from various literature, such as books, journals, and articles. By using the theory of deictic classification from Stephen Levinson (1983) as the main theory, the researcher intends to categorize and explain several demonstrative pronouns found in the Qur'an into several types of deixis based on their function. The researcher found that the demonstrative pronouns found in the Qur'an have 17 word forms. In addition, the demonstrative pronouns found only have the functions of personal deixis, discourse deixis, and spatial deixis.